Annotated list of ichthyofauna of inland and coastal waters of Sakhalin Island. 5. Families Cyclopteridae-Liparidae - Dyldin, Yury V.; Orlov, Alexei M. (Journal of Ichthyology, 2022)
The fifth part of the review represents the last part of the annotated list of fish species found in the marine (within a 200-mile zone), brackish, and fresh waters of Sakhalin: 84 species from one order Perciformes, one suborder Cottoidei, two families Cyclopteridae and Liparidae, and 13 genera. The review also represents general ecological characteristics of the ichthyofauna of Sakhalin, as well as a final essay.